2013
DOI: 10.1128/jvi.01055-13
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Characterization of Betacoronavirus Lineage C Viruses in Bats Reveals Marked Sequence Divergence in the Spike Protein of Pipistrellus Bat Coronavirus HKU5 in Japanese Pipistrelle: Implications for the Origin of the Novel Middle East Respiratory Syndrome Coronavirus

Abstract: While the novel Middle East respiratory syndrome coronavirus (MERS-CoV) is closely related to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
261
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 254 publications
(272 citation statements)
references
References 88 publications
7
261
0
4
Order By: Relevance
“…In the last 2 years, studies have shown that dromedaries are the hosts of at least two distinct coronaviruses. MERS-CoV is a lineage C betacoronavirus closely related to bat coronaviruses discovered by us (Lau et al, 2013b;Memish et al, 2013;Yang et al, 2014), whereas DcCoV UAE-HKU23 is a lineage A betacoronavirus closely related to other members of the species Betacoronavirus 1 found in humans and at least 15 other mammalian species (Woo et al, 2014b). Serological studies have shown that minimal cross-reactivity exists between MERS-CoV and DcCoV UAE-HKU23 (Woo et al, 2014b).…”
Section: Discussionmentioning
confidence: 99%
“…In the last 2 years, studies have shown that dromedaries are the hosts of at least two distinct coronaviruses. MERS-CoV is a lineage C betacoronavirus closely related to bat coronaviruses discovered by us (Lau et al, 2013b;Memish et al, 2013;Yang et al, 2014), whereas DcCoV UAE-HKU23 is a lineage A betacoronavirus closely related to other members of the species Betacoronavirus 1 found in humans and at least 15 other mammalian species (Woo et al, 2014b). Serological studies have shown that minimal cross-reactivity exists between MERS-CoV and DcCoV UAE-HKU23 (Woo et al, 2014b).…”
Section: Discussionmentioning
confidence: 99%
“…The lineage C betacoronaviruses Pipistrellus bat coronavirus HKU5 and Tylonycteris bat coronavirus HKU4 are genetically related to MERS-CoV and likely all emerged from a distant common ancestor centuries ago. 39 Lineage C betacoronaviruses identified in European and African Pipistrellus and Nycteris bats were determined to be genetically similar and phylogenetically related to MERSCoV. 7 Additionally, in Bisha, Saudi Arabia, a few months after the first human case of MERS-CoV infection was documented, a 190-nucleotide fragment of a coronavirus RNA-dependent RNA polymerase gene was amplified from bat feces and shared 100% sequence identity with the original MERS-CoV isolate from the same geographic region.…”
Section: Human Mers-cov Infectionsmentioning
confidence: 99%
“…To date, MERS-CoV has infected at least 77 people and was able to be transmitted from human to human. The genomic sequence of MERS-CoV is closely related to the sequences of certain bat coronaviruses (3)(4)(5), raising concerns over persistent bat-to-human cross-species transmission of the virus. The clinical signs and epidemic patterns of MERS-CoV are reminiscent of the severe acute respiratory syndrome coronavirus (SARS-CoV), the etiological agent of the worldwide SARS epidemic in 2002-2003 that infected more than 8,000 people with a ϳ10% fatality rate (6,7).…”
mentioning
confidence: 99%